A family of saturated controllers for UWMRs. (May 2020) - Moreno-Valenzuela, Javier; Montoya-Villegas, Luis; Pérez-Alcocer, Ricardo; Sandoval, Jesús
Abstract: Input saturation appears in a physical system when a large power dissipation is requested. In this situation, and specifically for unicycle-type wheeled mobile robots, actuators only can deliver a finite amount of power. Thus, in practice the linear and angular velocity input of this class of mobile robots is limited and this should be considered in the control design. In this paper, a family of controllers that produce saturated velocity input for unicycle-type wheeled mobile robots is presented. The proposed family of controllers is designed to satisfy the trajectory tracking control goal. Sufficient conditions to prove the closed-loop system global asymptotic stability are established by using Lyapunov's theory. Already reported schemes and original designs are shown to satisfy the properties of the given family of controllers. By using two different motion tasks, experimental tests in real-time with five saturated control schemes are presented in order to validate the proposed theory. In order to show the ability of the family of controllers to produce limited control action, experiments have also been carried out with an unsaturated algorithm. Better tracking accuracy is obtained with the original design derived from the proposed class of algorithms. Highlights: Input saturation in the control of mobile robots is a problem found in practice. Only a few solutions for this problem have been studied. A novel family of saturated controllers is given. A rigorous stability analysis that guarantees global asymptotic stability is given. An experimental validation of schemes belonging to the family is provided.